Structural determinants of the partial agonist-inverse agonist properties of 6′-azidohex-2′-yne-Δ(8)-tetrahydrocannabinol at cannabinoid receptors - Ross, Ruth A (1999)
1. We have extended previous investigations of four analogues of Δ(8)-tetrahydrocannabinol (Δ(8)-THC): 6′-azidohex-2′-yne-Δ(8)-THC (O-1184), 6′-azidohex-cis-2′-ene-Δ(8)-THC (O-1238) and octyl-2′-yne-Δ(8)-THC (O-584) and its 1-deoxy-analogue (O-1315). 2. O-1184, O-1238 and O-584 displaced [(3)H]-CP55940 from specific binding sites on Chinese hamster ovary (CHO) cell membranes expressing CB(1) or CB(2) cannabinoid receptors, with pK(i) values of 8.28 to 8.45 (CB(1)) and 8.03 to 8.13 (CB(2)). The pK(i) values of O-1315 were significantly less, 7.63 (CB(1)) and 7.01 (CB(2)). 3. All the analogues inhibited forskolin-stimulated cyclic AMP production by CB(1)-transfected CHO cells (pEC(50)=9.16 to 9.72). Only O-1238 behaved as a full agonist in this cell line. 4. In mouse vasa deferentia, O-1238 inhibited electrically-evoked contractions (pEC(50)=10.18 and E(max)=70.5%). Corresponding values for O-1184 were 9.08 and 21.1% respectively. At 1 nM, O-1184 produced surmountable antagonism of the cannabinoid receptor agonist, CP55940. However, at 0.1 nM, O-1184 did not attenuate CP55940-induced inhibition of cyclic AMP production by CB(1)-transfected CHO cells. 5. In CB(2)-transfected CHO cells, cyclic AMP production was inhibited by CP55940 (pEC(50)=8.59), enhanced by O-1184 and O-584 (pEC(50)=8.20 and 6.86 respectively) and not significantly affected by O-1238 or O-1315. 6. At 100 nM, O-1184 and O-1238 produced surmountable antagonism of CP55940 in CB(2) cells, decreasing the pEC(50) of CP55940 from 8.61 to 7.42 (O-1184) or from 8.54 to 7.44 (O-1238). 7. These data support the hypothesis that increasing the degree of unsaturation of the aliphatic side-chain of Δ(8)-THC analogues has little effect on CB(1) or CB(2) receptor affinity but can reduce CB(1) receptor efficacy and reverse the direction of responses elicited at CB(2) receptors.